2020
DOI: 10.16956/jes.2020.20.3.41
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profile Change after Thyroidectomy

Abstract: Purpose: Thyroid diseases and lipid metabolic abnormalities have been reported to be correlated. In patients with thyroid cancer, thyroid stimulating hormone levels are suppressed to prevent recurrence. Many studies have reported dyslipidemia associated with thyroid function, although its extent before and after thyroidectomy remains to be studied. This study aimed to determine the lipid levels for administering accurate lipid treatment in thyroid cancer patients post thyroidectomy. Methods: In total, 1,203 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In contrast, a recent systematic review and meta-analysis showed that dyslipidemia, including both hypercholesterolemia and hypertriglyceridemia, was not associated with TC (16). Further, Chu et al found no differences in the levels of cholesterol, LDL-C, triglyceride, and HDL-C before and after surgery in patients with TC, regardless of treatment modality (23). Nevertheless, most previous studies were conducted on a relatively small number of patients over a short period of time, whereas our study was based on a large cohort database with a follow-up period of over 7 years.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In contrast, a recent systematic review and meta-analysis showed that dyslipidemia, including both hypercholesterolemia and hypertriglyceridemia, was not associated with TC (16). Further, Chu et al found no differences in the levels of cholesterol, LDL-C, triglyceride, and HDL-C before and after surgery in patients with TC, regardless of treatment modality (23). Nevertheless, most previous studies were conducted on a relatively small number of patients over a short period of time, whereas our study was based on a large cohort database with a follow-up period of over 7 years.…”
Section: Discussionmentioning
confidence: 93%
“…Further, Chu et al. found no differences in the levels of cholesterol, LDL-C, triglyceride, and HDL-C before and after surgery in patients with TC, regardless of treatment modality ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thyroid hormone increases cholesterol production in the liver by inducing 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase activity. Cholesterol production rises in hyperthyroidism, although total blood cholesterol and low-density lipoprotein cholesterol (LDL-C) concentrations drop due to enhanced LDL-C metabolism [ 3 ]. Numerous factors contribute to accelerated atherosclerosis in hypothyroid individuals, including insulin resistance, hypercholesterolemia, enhanced low-density lipoprotein (LDL) oxidation, hypercoagulable condition, and increased peripheral vascular resistance.…”
Section: Introductionmentioning
confidence: 99%